Case Report: Thymic neuroendocrine tumor with metastasis to the breast causing ectopic Cushing’s syndrome - Zdrojowy-Wełna, Aleksandra; Bolanowski, Marek; Syrycka, Joanna; Jawiarczyk-Przybyłowska, Aleksandra; Kuliczkowska-Płaksej, Justyna (Frontiers in Oncology, 2025)
Ectopic adrenocorticotropic hormone secretion (EAS) is responsible for approximately 10%–18% of Cushing’s syndrome cases. Thymic neuroendocrine tumors (NETs) comprise 5%–16% of EAS; therefore, they are very rare and the data about this particular tumors is scarce. We present a case of a 34-year-old woman with a rapid onset of severe hypercortisolism in April 2016. After initial treatment with a steroid inhibitor (ketoconazole) and diagnostics including 68Ga DOTA-TATE PET/CT, it was shown to be caused by a small thymic NET. After a successful surgery and the resolution of all symptoms, there was a recurrence after 5 years of observation caused by a metastasis to the breast, shown in the 68Ga DOTA-TATE PET/CT result and confirmed with a breast biopsy. Treatment with a steroid inhibitor (metyrapone) and tumor resection were again curative. The last disease relapse appeared 7 years after the initial treatment, with severe hypercortisolism treated with osilodrostat. There was a local recurrence in the mediastinum, and a thoracoscopic surgery was performed with good clinical and biochemical effect. The patient remains under careful follow-up. Our case stays in accordance with recent literature data, showing that patients with thymic NETs are younger than previously considered and that the severity of hypercortisolism does not correlate with the tumor size. The symptoms of EAS associated with thymic NET may develop rapidly and may be severe as in our case. Nuclear medicine improves the effectiveness of the tumor search, which is crucial in successful EAS therapy. Our case also underlines the need for lifelong monitoring of patients with thymic NETs and EAS.